Do local governments tax homeowner communities differently? - Roland Füss; Oliver Lerbs (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
This paper investigates whether and how strongly the share of homeowners in a community affects residential property taxation by local governments. Different from renters, homeowners bear the full property tax burden irrespective of local market conditions, and the tax is more salient to them. "Homeowner communities" may hence oppose high property taxes in order to protect their housing wealth. Using granular spatial data from a complete housing inventory in the 2011 German Census and historical war damages as a source of exogenous variation in local homeownership, we provide empirical evidence that otherwise identical jurisdictions charge significantly lower property taxes when the share of homeowners in their population is higher. This result is invariant to local market conditions, which suggests tax salience as the key mechanism behind this effect. We find positive spatial dependence in tax multipliers, indicative of property tax mimicking by local governments.
urn:nbn:de:bsz:180-madoc-435656
Keywords: D72; H20; H31; H71; R31; 330; homeownership; public financing; residential property tax; spatial tax mimicking; yardstick competition